Waziri Tijjani and His Contributions for the Spread and Development of Tijjaniyya Sufi Order in Nigeria - Abubakar Ibrahim Adamu; Suleiman Ibrahim Abdulwahab (HISTORICAL: Journal of History and Social Sciences, 2024)
Islam as a practical religion on earth has penetrated almost all corners of the world. Tijjaniyyah also contributed for dissemination and the spread of Islam in Gombe. This research aims at an appraisal of the Sufi Roles in the Spread of Islam in Gombe Metropolis, with special reference to Waziri Tijjani of Gombe. The study begins with background of the study. It continues with explanation about the brief History of Gombe Metropolis, history of people in Gombe metropolis and other aspects of the people. It explain the introduction of Islam into Gombe Lands which helps one to understand the changes and transformations that occur later. It explain the roles played by Sufi order in spreading Islam into Gombe lands as a religion but also as general way of life. The research ends with elucidation of the changes and transformations of Islam and the role played by Sufi order. The findings reveal that, Sufi order played a vital role in the spread of Islam into Gombe lands alongside their norms and cultures. It also shows that Islam does not leave any loophole untouched in affairs of people particularly the people of Gombe. Analytical research methodology has been used in preparing this research. Data are drawn from interview, books, articles and scholarly journals.